The role of computer-mediated communication in the research process of music Sscholars: an exploratory investigation - Christine D. Brown (Information Research: An International Electronic Journal)
Music scholars' use and perceptions of the helpfulness of e-mailand electronic discussion groups are described. Diffusion of innovations theory is used to describe and assess the music scholars level of agreement with statements concerning the relative advantages and compatibility of e-mail and electronic discussion group use within the context of the research process. Data were collected via interviews and a survey administered to music scholars in Canada and the United States. Music scholars rated e-mail as consistently more helpful than discussion groups for selected activities in the research process. Scholars who found discussion groups not helpful in their research reacted by periodically unsubscribing, a pattern of intermittent discontinuance consistent with diffusion theory. These modes of computer-mediated communication were found to play marginal roles in the music scholar's research process.